2016
DOI: 10.1094/phyto-02-16-0084-fi
|View full text |Cite
|
Sign up to set email alerts
|

Cercospora zeinafrom Maize in South Africa Exhibits High Genetic Diversity and Lack of Regional Population Differentiation

Abstract: South Africa is one of the leading maize-producing countries in sub-Saharan Africa. Since the 1980s, Cercospora zeina, a causal agent of gray leaf spot (GLS) of maize, has become endemic in South Africa, and is responsible for substantial yield reductions. To assess genetic diversity and population structure of C. zeina in South Africa, 369 isolates were collected from commercial maize farms in three provinces (KwaZulu-Natal, Mpumalanga and North West). These isolates were evaluated with fourteen microsatellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…3 ). That most of these markers are not closely linked corroborates their usefulness where they have been used for population genetics studies of C. zeina isolates from East and southern Africa, and for future studies (Muller et al 2016 ; Nsibo et al 2019 , 2021 ). The genome assembly from long-read sequencing determined in this study (MVDW02) was confirmed to be derived from C. zeina .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…3 ). That most of these markers are not closely linked corroborates their usefulness where they have been used for population genetics studies of C. zeina isolates from East and southern Africa, and for future studies (Muller et al 2016 ; Nsibo et al 2019 , 2021 ). The genome assembly from long-read sequencing determined in this study (MVDW02) was confirmed to be derived from C. zeina .…”
Section: Resultsmentioning
confidence: 83%
“…Contig 20F did not have any significant BLASTN match other than to a C. zeina microsatellite sequence (CzSSR11) (Fig. 3 ) (Muller et al 2016 ). Contig 19F had sequence similarity to ribosomal RNA sequences including the 18S ribosomal RNA gene of various Mycosphaerellales including Cercospora sojina , Zymoseptora tritici , and Cladosporium fulvum .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the low level of genetic differentiation among sites was similar to the findings with C . zeina , which also had a lack of regional population differentiation [35]. …”
Section: Discussionmentioning
confidence: 99%